High Affinity Decynium-22 Binding to Brain Membrane Homogenates and Reduced Dorsal Camouflaging after Acute Exposure to it in Zebrafish - Georgianna G. Gould; Georgianna G. Gould; Priscilla A. Barba-Escobedo; Priscilla A. Barba-Escobedo; Rebecca E. Horton; Rebecca E. Horton; Lynette C. Daws; Lynette C. Daws; Lynette C. Daws (Frontiers Media S.A., 2022)
Organic cation transporters (OCTs) are expressed in the mammalian brain, kidney, liver, placenta, and intestines, where they facilitate the transport of cations and other substrates between extracellular fluids and cells. Despite increasing reliance on ectothermic vertebrates as alternative toxicology models, properties of their OCT homologs transporting many drugs and toxins remain poorly characterized. Recently, in zebrafish (Danio rerio), two proteins with functional similarities to human OCTs were shown to be highly expressed in the liver, kidney, eye, and brain. This study is the first to characterize in vivo uptake to the brain and the high-affinity brain membrane binding of the mammalian OCT blocker 1-1'-diethyl-2,2'cyanine iodide (decynium-22 or D-22) in zebrafish. Membrane saturation binding of [3H] D-22 in pooled zebrafish whole brain versus mouse hippocampal homogenates revealed a high-affinity binding site with a KD of 5 ± 2.5 nM and Bmax of 1974 ± 410 fmol/mg protein in the zebrafish brain, and a KD of 3.3 ± 2.3 and Bmax of 704 ± 182 fmol/mg protein in mouse hippocampus. The binding of [3H] D-22 to brain membrane homogenates was partially blocked by the neurotoxic cation 1-methyl-4-phenylpyridinium (MPP+), a known OCT substrate. To determine if D-22 bath exposures reach the brain, zebrafish were exposed to 25 nM [3H] D-22 for 10 min, and 736 ± 68 ng/g wet weight [3H] D-22 was bound. Acute behavioral effects of D-22 in zebrafish were characterized in two anxiety-relevant tests. In the first cohort of zebrafish, 12.5, 25, or 50 mg/L D-22 had no effect on their height in the dive tank or entries and time spent in white arms of a light/dark plus maze. By contrast, 25 mg/L buspirone increased zebrafish dive tank top-dwelling (p < 0.05), an anticipated anxiolytic effect. However, a second cohort of zebrafish treated with 50 mg/L D-22 made more white arm entries, and females spent more time in white than controls. Based on these findings, it appears that D-22 bath treatments reach the zebrafish brain and have partial anxiolytic properties, reducing anti-predator dorsal camouflaging, without increasing vertical exploration. High-affinity binding of [3H] D-22 in zebrafish brain and mouse brain was similar, with nanomolar affinity, possibly at conserved OCT site(s).